Penyesuaian Keluarga, Pengasuhan, Kekerasan dalam Pengasuhan, dan Agresivitas pada Anak Usia Sekolah - Ismayanti Pratiwi; Dwi Hastuti; Istiqlaliyah Muflikhati (Jurnal Ilmu Keluarga dan Konsumen, 2018)
Inappropriate parenting can trigger emotional problems that lead to negative behavior, one of that is aggressiveness. This study aimed to analyze the effect of family adjustment, parenting, and violence in parenting on aggressiveness in among elementary school-age children. This study used a cross-sectional study design. Samples of the research were 99 families who had elementary school children and mother involved as child respondents. The study was conducted in West Bogor Subdistrict, Bogor City. The participants were choose by random cluster sampling in two selected public schools. The analysis used descriptive statistics, independent sample t-test and path analysis (path analysis). The results found that family adjustment (72,29) and parenting (63,86) had not been done optimally yet. Parenting violence was also still found in the study (14,22). Aggressiveness has begun to appear in elementary school-age children (26,44). The study found no differences in family adjustment, parenting, violence in parenting and aggressiveness in boys and girls. Meanwhile, based on variable dimensions, there are differences in cooperation in parenting, neglect parenting, and physical aggressiveness between boys and girls. The results of the analysis show that gender influenced the aggressiveness. The family adjustment had an indirect effect on aggressiveness, through parenting. Parenting has a direct negative effect on aggressiveness. Conversely, negative parenting had a direct positive effect on aggressiveness.